1984
DOI: 10.1080/00365521.1984.12005800
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy in Crohn's Disease

Abstract: Over a 13-year period, the course of 109 pregnancies in 68 women with Crohn's disease was studied. A total of 76 children were delivered. There were no gemellary deliveries, and none of the children had congenital malformations. Pregnancy entailed no increased risk of an exacerbation of the bowel disease. As compared with the reference population and with women with ulcerative colitis, the total material showed an increased risk of premature delivery and spontaneous abortion, but a further analysis showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
89
0
10

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(107 citation statements)
references
References 17 publications
8
89
0
10
Order By: Relevance
“…Specifically, Nielsen reported UC flare rates of 34 versus 32% in pregnant and nonpregnant women, respectively. A similar finding was seen among CD patients [28]. A large northern California population-based cohort study of 461 pregnant IBD patients showed the majority of patients with UC and CD had inactive or mild disease throughout pregnancy (65-80% based on the pregnancy stage) [29].…”
Section: Effect Of Pregnancy On Disease Activitysupporting
confidence: 51%
See 1 more Smart Citation
“…Specifically, Nielsen reported UC flare rates of 34 versus 32% in pregnant and nonpregnant women, respectively. A similar finding was seen among CD patients [28]. A large northern California population-based cohort study of 461 pregnant IBD patients showed the majority of patients with UC and CD had inactive or mild disease throughout pregnancy (65-80% based on the pregnancy stage) [29].…”
Section: Effect Of Pregnancy On Disease Activitysupporting
confidence: 51%
“…Earlier studies showed active disease at conception was associated with a higher rate of fetal loss [52] and preterm birth [9,28]. Disease activity during pregnancy has also previously been associated with preterm birth and low birthweight [37,46,53,54].…”
Section: Effect Of Ibd On Pregnancy Course and Pregnancy Outcomesmentioning
confidence: 99%
“…Complications associated with IBD activity at the time of conception include: Abortion, low birth weight (LBW), and premature births [50,[52][53][54][55] . These complications again, are usually seen more often in CD patients than UC patients.…”
Section: Pregnancymentioning
confidence: 99%
“…Quanto aos efeitos da RC e da DC sobre a gravidez, estudos demonstraram uma taxa de proles saudáveis, similar à taxa da população em geral [2,5,6]. Trabalhos demonstraram que se a doença estiver quiescente durante a gestação, não há aumento do risco de abortamento espontâneo, complicações relacionadas à gestação, anomalias congênitas ou outras intercorrências com o feto [7,8,9,10,11,12,13,14,15].…”
Section: Introductionunclassified
“…Nesta situação há maior incidência de abortamento espontâneo, prematuridade e outras alterações perinatais, parecendo ser maior na DC do que na RC. [5,7,13,15,18,19,20,21]. Há trabalhos que demonstraram maior incidência de recém-nascidos de baixo peso e pré-termos e risco de abortamento espontâneo em mães com doença inflamatória intestinal, principalmente na DC em atividade, no momento da concepção [5,18,22,23].…”
Section: Introductionunclassified